PEMBERDAYAAN PETANI DENGAN PEMANFAATAN LAHAN TIDUR UNTUK PERTANIAN BIOFARMAKA DI KECAMATAN DAWE KABUPATEN KUDUS - Dicky Setyawan; Sulistyowati .; Puji Astuti (Journal of Politic and Government Studies, 2016)
This research aims to determine the government's efforts to empower farmers to utilize unutilized land for farming of medicinal plants as well as the wonted obstacles experienced . In this study researchers used qualitative research methods to the type of primary data and secondary data collection techniques used were interviews and documentation . The results showed that the unutilized land in District Dawe in 2013 mostly used by farmers to grow medicinal plants covering an area of 118 Hectaracre , which became the main commodity of medicinal plants in the Dawe subdistric is a ginger plant , kencur , and laos . Empowerment Department of Agriculture Fisheries and Forestry Kudus District can be quite successful with some obstacles . The government should conduct a review of the empowerment program and increase the number of extension , in order to more evenly in the Dawe subdistric , as well as seek to establish cooperation with the company herbal medicinal plants so that farmers can be helped in terms of marketing .Keywords : Empowering farmers, unutilized land, medicinal plants